Sistem Pendukung Keputusan Penilaian Kinerja Manajer di PT. Pos Indonesia dengan Metode WASPAS - Dwi Asdini; Miftahul Khairat; Dito Putro Utomo (JURIKOM (Jurnal Riset Komputer), 2022)
PT. Pos Indonesia is one of the State-Owned Enterprises (BUMN) which is engaged in shipping services. To face this business competition, a company must improve the quality of service to obtain customer satisfaction and maintain the smoothness and progress of the business. The improvement of the service process for the company cannot be separated from the role and contribution of a manager in the company. So that the feasibility of the performance of a manager must of course be considered and also assessed. To see the feasibility of a PT. Pos Indonesia manager doing a performance assessment. To get accurate performance appraisal results, a decision support system is carried out using the WASPAS method. Where the WASPAS method is considered appropriate to determine the best technician because it performs ranking based on predetermined criteria values. It is hoped that this research can help get effective results. In the study, it was found that managers were still eligible to be in the occupied positions